3D flower like δ-MnO2/MXene Nano-hybrids for the removal of hexavalent Cr from wastewater. Issue 18 (15th September 2021) - Khan, Abdul Rehman; Awan, Sheheryar Khan; Husnain, Syed M.; Abbas, Nadir; Anjum, Dalaver H.; Abbas, Naseeem; Benaissa, Mhamed; Mirza, Cyrus Raza; Mujtaba-ul-Hassan, Syed; Shahzad, Faisal
Abstract: Herein, 3D flower-like δ-MnO2, MXene and δ-MnO2 /MXene in-situ hybrid (IH) composites were prepared (via hydrothermal and solution treatment methods) for the effective removal of Cr (VI) from the contaminated water. The effect of various experimental parameters including contact time, pH levels and initial Cr (VI) ions concentration was determined and compared under static conditions. The kinetics of Cr (VI) adsorption onto δ-MnO2, MXene, and IH confirmed the existence of a pseudo-second-order model. The obtained results reveal that the removal of Cr (VI) largely depends on the pH of the solution. The adsorption isotherm data fits best for Freundlich model, illustrating a multi-site adsorption mechanism of Cr (VI) ion on these adsorbents. The maximum Cr (VI) adsorption capacities onto δ-MnO2, MXene and IH are 235.65 mg g −1, 273.1 mg g −1 and 353.87 mg g −1, respectively. The study reveals that hetero-engineered approach of synthesizing transition metal oxides with MXenes provides abundant opportunities to remove contaminants from water with better efficiency due to reduction and electrostatic interaction.